2002
DOI: 10.1177/108705710200700307
|View full text |Cite
|
Sign up to set email alerts
|

Functional Screening of G Protein–Coupled Receptors by Measuring Intracellular Calcium with a Fluorescence Microplate Reader

Abstract: Ligand binding studies reveal information about affinity to G protein—coupled receptors (GPCRs) rather than functional properties. Increase in intracellular Ca2+appears to represent a universal second messenger signal for a majority of recombinant GPCRs. Here, we exploit Ca2+signaling as a fast and sensitive functional screening method for a number of GPCRs coupled to different G proteins. Ca2+fluorescence measurements are performed using Oregon Green 488 BAPTA-1/AM and a microplate reader equipped with an inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 42 publications
0
68
0
Order By: Relevance
“…Calcium fluorescence measurements in cholangiocytes were performed using fluo-3 AM (Molecular Probes, Eugene, OR) and a Fluoroskan Ascent FL (ThermoLabsystems, Helsinki, Finland) microplate reader equipped with three injectors. 11,27 Cholangiocytes (4 ϫ 10 4 per well) were loaded for 1 hour at room temperature with 5 mol/L of fluo-3 AM in Tyrode's salt solution (137 mmol/L NaCl, 2.7 mmol/L KCl, 1 mmol/L MgCl 2 , 0.2 mmol/L NaH 2 PO 4 , 12 mmol/L NaHCO 3 , and 5.5 mmol/L glucose) with 0.1% Pluronic F-127 (Molecular Probes). After washes with Tyrode's salt solution, the loaded cells were added to a 96-well black microplate.…”
Section: Purification Of Cholangiocytes and Ibdusmentioning
confidence: 99%
“…Calcium fluorescence measurements in cholangiocytes were performed using fluo-3 AM (Molecular Probes, Eugene, OR) and a Fluoroskan Ascent FL (ThermoLabsystems, Helsinki, Finland) microplate reader equipped with three injectors. 11,27 Cholangiocytes (4 ϫ 10 4 per well) were loaded for 1 hour at room temperature with 5 mol/L of fluo-3 AM in Tyrode's salt solution (137 mmol/L NaCl, 2.7 mmol/L KCl, 1 mmol/L MgCl 2 , 0.2 mmol/L NaH 2 PO 4 , 12 mmol/L NaHCO 3 , and 5.5 mmol/L glucose) with 0.1% Pluronic F-127 (Molecular Probes). After washes with Tyrode's salt solution, the loaded cells were added to a 96-well black microplate.…”
Section: Purification Of Cholangiocytes and Ibdusmentioning
confidence: 99%
“…Recently, a functional assay based on the change in intracellular Ca 2+ upon agonist stimulation was described for differently coupled GPCRs (G s , G, Gq). 11 In this report, it was shown that compounds described in the literature as agonists at D1 and/or D2 receptors are indeed capable of inducing a Ca 2+ signal ( Table 3). The specificity of this signal was proved by antagonist injection, which did not yield a Ca 2+ response (Figure 1 , Figure 2), and by injection of agonists into control cells lacking dopamine receptor expression (HEK293 wildtype cells, data not shown).…”
Section: Discussionmentioning
confidence: 70%
“…These data suggest that apparent functional and radioligand binding K values are significantly correlated but that an increase in radioligand binding yields a smaller increase in functional effects (measured as Ca D2 receptors (B), respectively. K i of LE300 was estimated as previously described [11]. Apparent functional K i values were obtained by measuring the inhibition of agonist (100nM SKF38393 at D1, 30nM quinpirole at D2 receptors) induced increase in intracellular Ca 2+ after preincubation with the respective test compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GIRK channels) (20), I h and other K+ channels (21), high-voltage gated calcium channels (L-type, P/Q/R-type and N-type calcium channels) (22; 23), and also sodium channels (24; 25). D1 receptors furthermore have the effect of increasing NMDA transmission (26; 27), and may have complex effects on local calcium levels (28).…”
Section: Protein Regulatory Networkmentioning
confidence: 99%